Electoral cycles in international reserves: Evidence from Latin America and the OECD - Jorge M. Streb; Daniel Lema; Pablo Garofalo (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2013)
In Latin America there is ample evidence of exchange rate depreciations after elections. Hence, we turn to the behavior of international reserves over the 1980-2005 period to investigate if exchange rates are temporarily stabilized before elections. Using annual, quarterly, and monthly data to define the election year, we find that international reserves fall significantly before elections, which indeed suggests a policy of stabilizing exchange rates. The patterns observed in the region are not replicated in OECD countries. However, once we control for legislative checks and balances on executive discretion in countries with strong compliance with the law, the behavior of both regions becomes remarkably similar. We find that lower effective checks and balances can explain why reserves fall before elections in Latin America. The electoral cycles in reserves and exchange rates in Latin America can be interpreted in terms of the fiscal dominance of monetary policy.
Keywords: D72; D78; H60; 330; monetary policy; checks and balances; fiscal dominance; political budget cycles; temporal aggregation